Landscape as built heritage, a consideration towards urban planning - Peña Guillén, Victor (2018)
The concept of Cultural Heritage has become a conservation paradigm for those urban landscape components of outstanding cultural and historical value. Since the beginnings of modern era, its definition has experienced a conceptual evolution by incorporating progressively first objects and monuments, then cities and landscapes, and finally human communities (Sonkoly, 2010). Landscape is a term that allows study and understanding of built heritage, because now its meaning integrates the dynamic and complex urban systems. Antrop (2008) stated that landscape has been broadening its significance to become a “field of action for temporal and spatial processes”. Current document integrates built cultural heritage concept from a landscape theoretical approach, and towards its application onto an urban planning scheme. Another approach called Historic Urban Landscape (Unesco, 2011) helps providing an conceptual framework for this task, which is hypothesized as useful for built heritage planning and management at a landscape scale.